Penerapan Model Pembelajaran Problem Based Learning (PBL) Untuk Meningkatkan Hasil Belajar Siswa Materi Laporan Keuangan - Pramitha, Devanda Arly; Wahjudi, Eko (Jurnal Pendidikan Ekonomi Undiksha, 2020)
The purpose of this study is to analyze whether the Problem Based Learning (PBL) learning model can improve student learning outcomes of service company financial statements. This type of research is library research or literature study. The results obtained based on previous research, it is found that the Problem Based Learning (PBL) learning model can improve student learning outcomes in the material of financial services companies. This is because the Problem Based Learning (PBL) learning model can improve students' learning abilities to think critically, solve problems, and be able to organize their knowledge by going through the process of solving a problem that has been implemented. This shows that this learning model is appropriate and relevant to be applied in financial statement material because in that material requires direct skills and deeper understanding so students can better understand a material if they must be directed to a real problem and must be resolved.